An options-based analysis of emerging market exchange rate expectations: Brazil's Real Plan, 1994-1999. - Campa, José M.; Chang, P. H. Kevin; Refalo, James F. (Journal of Development Economics, 2002)
This paper uses currency option data to investigate market expectations on the Brazilian Real-U.S. dollar exchange rate from October 1994 through March 1999. We derive implied probability density functions (PDF) for expected future exchange rates and thus measures of the credibility of the “crawling peg” and target zone regimes governing the exchange rate. Target zone credibility was poor prior to February 1996, improved afterwards through September 1997 and later started to worsen again. The market anticipated periodic band adjustments and estimated distributions are very sensitive to political and economic news affecting the credibility of the regime. Copyright (c) 2002 Elsevier Science B.V.